Validasi Skor PEACH sebagai Prediktor Mortalitas Selama Rawatan Paska Operasi Penyakit Jantung Bawaan Pada Dewasa di Rumah Sakit Umum Pusat Haji Adam Malik Medan - Zebua, Juang Idaman; Nasution, Ali Nafiah; Ketaren, Andre Pasha; Hasan, Harris; Akbar, Nizam Zikri (The Indonesian Heart Association, 2023)
Introduction: Congenital heart disease (CHD) is an abnormality in the structure and function of the heart that is acquired while still intrauterine where the incidence of CHD worldwide is estimated at around 8 cases per 1,000 live births. Even though the development of the medical science is currently advanced, there are still CHD patients who are lately diagnosed and found when the patient is an adult so it requires surgical interventions. The PEACH score is a score that can predict postoperative in-hospital mortality in adults CHD patients. This study aims to validate the PEACH score. Methods: This is a retrospective cohort study of 52 adult patients with CHD who underwent surgery at Haji Adam Malik General Hospital from January 2019 to April 2023. Validation was analyzed using a calibration and discrimination test to the PEACH score in predicting postoperative in-hospital mortality. Result: The incidence of in-hospital mortality was 8 (15.4%) patients. There is a relationship between the PEACH score group and the incidence of mortality (p=0.006). The results of the calibration test using the Hosmer and Lameshow analysis and the discrimination test using the Receiver Operating Characteristic analysis showed good validation (p=0.85; AUC=0.83). Conclusion: The PEACH score is valid for predicting postoperative in-hospital mortality in adult congenital heart disease at Haji Adam Malik General Hospital.This article has a related Erratum.